The Law Enforcement On Phornographic Cases - Nanda Setya Laksana; Achmad Sulchan (Law Development Journal, 2021)
This study aims to determine the form of law enforcement against pornography in the investigation process as well as to find out the obstacles faced and provide solutions in overcoming the crime of pornography according to Act No. 44 of 2008, and also to find out the judges' considerations in deciding criminal cases of pornography in the Jepara District Court with case number 138/Pid.B/2018/PN.Jpa, and to find out the law enforcement of pornography crimes based on Act No. 44 of 2008 concerning pornography. This research was carried out at the Jepara District Court. To achieve the objectives of the study, the researchers used data collection methods: interview methods, library methods, and data analysis methods related to the discussion being studied. The conclusion of this research isBased on the facts revealed at the trial, the defendant has been proven to have fulfilled all the elements of the article and in the trial there were no things that could abolish the crime, both justifying reasons and excuses, while for the philosophical and sociological aspects, what was considered by the Panel of Judges was because The defendant's actions violated the norms of decency in society. So that the sentence is very appropriate to be handed down to the defendant so that there is a sense of justice in the community.